Integration of Evidence on Community Cancer Risks from Elongate Mineral Particles in Silver Bay, Minnesota. Issue 9 (2nd February 2021) - Dell, Linda D.; Gallagher, Alexa E.; Yost, Lisa J.; Mundt, Kenneth A.
Abstract: The potential for cancer‐related risks to community members from ambient exposure to elongate mineral particles (EMPs) in taconite processing has not been formally evaluated. We evaluated 926 ambient air samples including 12, 928 EMPs (particle structures with length‐to‐width ratio ≥3:1) collected over 26 years near a taconite processing facility in Silver Bay, Minnesota. Eighty‐two percent of EMPs were ≤3 μm in length and 97% of EMPs had an average aspect ratio <20:1. A total of 935 (7.3%) EMPs had length >5 μm and AR ≥3:1. Average ambient concentration of NIOSH countable amphibole EMPs over all years was 0.000387 EMPs per cubic centimeter (EMP/cm 3 ). Of 12, 765 nonchrysotile EMPs, the number of amphiboles with length and width dimensions that correlate best with asbestos‐related carcinogenicity ranged from four (0.03%) to 13 (0.1%) and the associated ambient amphibole air concentrations ranged from 0.000003 to 0.000007 EMP/cm 3 . After 65 years of taconite processing in Silver Bay, evidence of an increased risk of mesothelioma and lung cancer in community members who did not work in the taconite industry is lacking. The absence of an increased risk of asbestos‐related cancer in the Silver Bay community is coherent with supporting evidence from epidemiological and toxicological studies, as well as ambient exposure data and lake sediment data collected in Minnesota Iron Range communities. Collectively, the data provide consistent evidence that nonasbestiform amphibole minerals lack the carcinogenic potential exhibited by amphibole asbestos.